2004
DOI: 10.1136/jcp.2003.012922
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous manifestations of thyroid cancer: a report of four cases and review of the literature

Abstract: Cutaneous metastases from thyroid carcinoma are rare. This report describes four cases of thyroid carcinoma metastatic to the skin. Two cases were medullary carcinoma and two were papillary thyroid carcinoma. In two cases, skin metastases were the presenting feature of the underlying thyroid carcinoma. Examination of the skin lesions by conventional light microscopy suggested the possibility of metastatic carcinoma and immunohistochemical tests confirmed the diagnosis. Subsequent investigations identified prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 20 publications
0
72
0
3
Order By: Relevance
“…Additional neuroendocrine markers such as synaptophysin, chromogranin and CD 56 can be identified by IHC staining to diagnose MTC metastases. [6] Thyroid transcription factor-1 (TTF-1) is a 38 kd DNA binding protein, originally detected in follicular cells of the thyroid, thyroid C cells and subsequently in pneumocytes.…”
Section: Immunohistochemical Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additional neuroendocrine markers such as synaptophysin, chromogranin and CD 56 can be identified by IHC staining to diagnose MTC metastases. [6] Thyroid transcription factor-1 (TTF-1) is a 38 kd DNA binding protein, originally detected in follicular cells of the thyroid, thyroid C cells and subsequently in pneumocytes.…”
Section: Immunohistochemical Methodsmentioning
confidence: 99%
“…[5,6,[30][31][32] In five cases scalp was the only cutaneous site of metastasis and in one case chest wall was also involved. Alwaheeb et al [6] reported 2 cases of MTC presenting initially with scalp nodules. In the other 4 cases scalp lesions were detected 1 to 4 years after the diagnosis of primary MTC.…”
Section: Medullary Carcinomamentioning
confidence: 99%
See 2 more Smart Citations
“…These findings were helpful for making a diagnosis of multiple metastases of poorly differentiated thyroid carcinoma and were also useful in following up of treatment response to anti-cancer chemotherapy. The skin metastasis of thyroid carcinoma is a disseminated tumor, and it has a poor prognosis to such an extent that its mean survival is at most 7.5∼19 months (3,4). To date, due to a small number of cases of thyroid medullary cancer, a statistical significance could not be analysed.…”
Section: Case Reportmentioning
confidence: 99%